AN ANALYSIS OF THE QUALITY OF TEACHER-MADE MULTIPLE-CHOICE TEST USED AS SUMMATIVE ASSESSMENT FOR ENGLISH SUBJECT - Septi, Ni Kadek Dwi Candra; Paramartha, A.A. Gede Yudha; Eka Wahyuni, Luh Gede (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2020)
Assessment is an important part in teaching and learning process. An instrument that is used to assess the students’ level must be high in quality by following certain standard in constructing the instrument itself. This research is a descriptive research that aimed to investigate the quality of teacher-made multiple-choice tests that were used as summative assessment in middle test for English subject at SMP N 4 Singaraja. There are 125 items in total from 4 teacher-made multiple-choice tests. The data were collected by using document study and interview as the method with the assistance of checklist and interview guide as the instrument. The data was analyzed by comparing each item in the multiple-choice tests with a set of norms to find the congruity and further to be classified to determine the quality.  The result shows that all of the teacher-made multiple-choice tests have a very good quality where 124 (99%) out of 125 items are qualified as very good and only 1 (1%) item is qualified as good. Some improvement is needed by paying more attention specifically for the unfulfilled norms.